Quantitative proteomics on the cerebrospinal fluid of hydrocephalus in neonatal bacterial meningitis - Chen, Juncao; Huang, Weiben; Zhang, Hong; Peng, Xiangwen; Yang, Jun; Yang, Yong; Su, Jinzhen; Wang, Siyao; Zhou, Wei (Frontiers in Pediatrics, 2022)
Objective: Hydrocephalus in bacterial meningitis is a devastating infectious neurological disease and the proteins and pathways involved in its pathophysiology are not fully understood. Methods: Label-free quantitative proteomics analyses was used to identify differentially expressed proteins (DEPs) in cerebrospinal fluid (CSF) samples from infants with hydrocephalus and bacterial meningitis (HBM group, N= 8), infants with bacterial meningitis (BM group, N= 9); and healthy infants (N group, N= 11). Bioinformatics analysis was subsequently performed to investigate Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) enriched signaling pathways of these DEPs. Six proteins (AZU1, COX4I1, EDF1, KRT31, MMP12, and PRG2) were selected for further validation via enzyme-linked immunosorbent assay (ELISA). Results: Compared with BM group and N group, HBM group had a higher whole CSF protein level (5.6 ± 2.7 vs.1.7 ± 1.0 vs. 1.2 ± 0.5 g/l) and lower whole CSF glucose level (0.8 ± 0.6 vs. 1.8 ± 0.7 vs. 3.3 ± 0.8 mmol/l) (both P < 0.05). Over 300 DEPs were differentially expressed in HBM group compared with BM group and BM compared with N group, of which 78% were common to both. Cluster analysis indicated that the levels of 226 proteins were increased in BM group compared with N group and were decreased in HBM group compared with BM group. Bioinformatics analysis indicated the involvement of the cell adhesion, immune response and extracellular exosome signalling were significantly enriched in HBM compared with BM group and BM compared with group. 267 DEPs were identified between HBM group with N group, KEGG analysis indicated that DEPs mainly involved in filament cytoskeleton and immune response. The ELISA results further verified that the expression levels of AZU1 were significantly different from among three groups (both P < 0.05). Conclusion: This is the first reported characterization of quantitative proteomics from the CSF of infants with hydrocephalus and bacterial meningitis. Our study also demonstrated that AZU1 could be a potential biomarker for the diagnosis of hydrocephalus in bacterial meningitis.